Recent advances in transition-metal-free arylation reactions involving hypervalent iodine salts - Mamgain, Ritu; Sakthivel, Kokila; Singh, Fateh V. (Beilstein Journal of Organic Chemistry, 2024)
Diaryliodonium salts have become widely recognized as arylating agents in the last two decades. Both, symmetrical and unsymmetrical forms of these salts serve as effective electrophilic arylating reagents in various organic syntheses. The use of diaryliodoniums in C–C and carbon–heteroatom bond formations, particularly under metal-free conditions, has further enhanced the popularity of these reagents. In this review, we concentrate on various arylation reactions involving carbon and other heteroatoms, encompassing rearrangement reactions in the absence of any metal catalyst, and summarize advancements made in the last five years.
Keywords: arylation reaction; diaryliodonium salts; electrophilic arylation reagent; metal-free arylation; rearrangement reaction